Análise histológica, histoquímica, histométrica e ultraestrutural de intestinos de jacaré-do-pantanal (Caiman yacare DAUDIN, 1802) (Crocodilia: Reptilia) criado em cativeiro - Aleixo, Victor Manuel (2011)
The commercial breeding of the Caiman yacare has been consolidated in the state of Mato Grosso as an alternative and as a legal activity for rural properties in the area of its natural occurrence, restraining predatory hunting and collaborating to the preservation of the species. The rationalization of the production process into the caiman's breading is a relatively new action, which allows obtaining better skin quality and its integral use, different from those originated from animals living in wildlife. Considering the importance of the intestines as the main organ where the major events related to obtaining nutrients for the body metabolism occur, this study aimed at characterizing qualitative and quantitatively the mucosa of the small and large intestine of the C. yacare. For the characterization of the intestinal wall structure and histometry of the mucosa, intestinal samples from 16 animals were collected for the study in the optical microscope and two others for the study in the scanning electron microscope. The samples were obtained and processed according to the respective protocols, in five regions, four from the small intestine and one from the large intestine. The stains were hematoxylin, eosin, Mallory trichomo and Picrossirius, and the histochemical techniques consisted of the reaction to periodic acid-Schiff and alcian blue pH 1.0 counterstained with hematoxylin and alcian blue pH 2.5 conjugated to periodic acid-Schiff. Histometric study was used in the analysis of variance and Neuwman-Keuls test. For the description of histological structures it was used the terminology available in Nomina Histology. The wall structure of small and large intestine of the C. yacare was composed of the tunica mucosa, muscular and serosa. The mucosa was composed of epithelial lining like the simple cylindrical type made by epithelial columnar cells of the villus and goblet cells; characteristic lamina of loose connective tissue and muscular tissue from the single mucosa. The composition of the secretion of goblet cells ranged from neutral to acid. It was not observed the presence of intestinal glands. The muscular layer consisted of two decks, the circular and the longitudinal, the former being the most developed. The serosa was typical. The specializations of the mucosa observed in the small and in the large intestine, respectively, were intestinal villi and folds, and alongside the regions of the intestine, showed a reduction of its complexity. The histometric study of the mucosa showed a statistically significant difference between the small and the large intestine. The scanning electron microscopy revealed the presence of one type of ridge or fold in the duodenum and two types in the other regions analyzed. They showed variation in shape, spacing, height and scale between the regions. Although the structure of the intestinal wall of C. yacare is similar to those of other crocodilians, of the green turtle and of the ostrich, it is still necessary to carry out studies about the histophysiology so that the nutritional management of the species in captivity is improved.